1970
DOI: 10.1104/pp.45.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Indoleacetic Acid Oxidase Activity of Winter Wheat by Cold Treatment and Gibberellic Acid

Abstract: The activity of indoleacetic acid oxidase increased 10-fold during 40 days of cold treatment of winter wheat seedlings. Puromycin and 6-methyl purine inhibited indoleacetic acid oxidase development in the cold. Addition of gibberellic acid stimulated indoleacetic acid oxidase development during germination at room temperature and during cold treatment. Amo-1618 inhibited indoleacetic acid oxidase development before and during cold treatment. Indoleacetic acid treatment increased indoleacetic acid oxidase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Plant tissues capable of rapid growth have been found to exhibit low IAA oxidase activity, whereas higher levels of activity were observed in slower growing tissues (Galston and Dalberg, 1954;Bolduc et al, 1970;Darbyshire, 1971). Evidence for an inverse relationship between IAA oxidase activity and endogenous IAA level has been reported (Khan, 2003;Alagarswamy et al, 2004;Parmar and Chanda, 2005).…”
Section: Iaa-deficiency In Zs97a Paniclementioning
confidence: 99%
“…Plant tissues capable of rapid growth have been found to exhibit low IAA oxidase activity, whereas higher levels of activity were observed in slower growing tissues (Galston and Dalberg, 1954;Bolduc et al, 1970;Darbyshire, 1971). Evidence for an inverse relationship between IAA oxidase activity and endogenous IAA level has been reported (Khan, 2003;Alagarswamy et al, 2004;Parmar and Chanda, 2005).…”
Section: Iaa-deficiency In Zs97a Paniclementioning
confidence: 99%
“…Recent studies have shown levels of IAA oxidase activity may be affected by environmental stress in the form of low temperatures (20) or water stress BA at 2 x 10 M using corn ( Zea mays L. ) . Two days after spraying, plants were chilled at -2°C for 3 hours.…”
Section: Growth Regulators and Chilling Injury In Plantsmentioning
confidence: 99%
“…Subsequent work with rice seedlings (10) did not support the thesis that interaction between the hormones proceeds via an auxin-sparing system, albeit that IAA oxidase appears to control coleoptile elongation in this tissue. Other investigators have reported no effect of GA on IAA oxidase (3,26), and recently GA has been shown to increase the oxidase activity (2,7). Since the evidence presented here indicates that GA increases IAA oxidase activity, our work does not support a hypothesis based on an auxin-sparing system.…”
Section: Promotion Of Iaa Oxidation By Ga3mentioning
confidence: 99%